2019
DOI: 10.1097/md.0000000000016416
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiologists’ acquisition of hepatitis B virus infection

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…of CHW having completed the HB vaccination standard, respectively. Such data are worrisome, considering that the WHO 3 and the Brazilian Ministry of Health 7 recommend 100% vaccination against HB among health workers, since lack of vaccination exposes these professionals to the risk of HB virus (HBV) infection 3,5,12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of CHW having completed the HB vaccination standard, respectively. Such data are worrisome, considering that the WHO 3 and the Brazilian Ministry of Health 7 recommend 100% vaccination against HB among health workers, since lack of vaccination exposes these professionals to the risk of HB virus (HBV) infection 3,5,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, Brazilian surveys have showed inadequate adherence of health-care professionals to HB vaccination [8][9][10][11] . Recent publications report important differences in HB vaccination adherence among the countries [12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arghittu et al [8] found that only 30.6% HCWs in an Italian University Hospital had the "flu vaccination". Tian et al [9] found that among 1739 Chinees anesthesiologists, 91.9% were exposed to sharps injuries, and 79.4% received three "HBV vaccination doses". However, half of them received reminder HBV vaccination doses.…”
Section: Introductionmentioning
confidence: 99%